14th CIRIAF National Congress - Energy, Environment and Sustainable Development - Francesco Asdrubali (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
CIRIAF (Inter-University Research Center on Pollution and Environment "Mauro Felli" is a research center, based at the University of Perugia, which promotes interdisciplinary research activities in the fields of environmental pollution and its health and socio-economic effects, sustainable development, renewable and alternative energy, energy planning, and sustainable mobility. One hundred professors from fourteen different Italian universities are involved in the activities of the center. The CIRIAF National Congress (e.g., the fourteenth one in 2014), has become, over time, an important event for researchers and experts (engineers, physicists, chemists, architects, doctors, and economists). These individuals are not simply academics; they also hail from ministries, environmental agencies, and local authorities. The annual meeting in Perugia is an opportunity to discuss the issues related to energy, environment and sustainable development. After some editions were devoted to panel discussions and workshops, the 14th Congress, which took place in Perugia from 4-5 April 2014, returned to the formula of parallel technical sessions. The Congress was quite successful. Seventy-nine papers were presented during the Congress; these were divided into the following eight Sessions, in line with the congress tradition. The session topics are of great contemporary interest: Built Environment Quality and Indoor Pollution Energy and Environmental Certification of Buildings Artworks Preservation and Museum Plants Renewable and Alternative Energy Sources and Systems Pollution from Physical Agents (noise, vibrations, electromagnetic fields) Air and Water Pollution Sustainable Mobility Energy Planning and Environmental Impact As usual, the ceremony of the "Mauro Felli" award took place during the Congress. The award, established to honor the memory of the founder and first Director of CIRIAF, is intended for young graduates, Ph.D. students or researchers who have carried out research activities in the fields concerning pollution originating from physical agents, the effects of environmental pollution on humans or related issues. Thanks to an agreement with the international publishing house MDPI, I am happy to introduce to you a special issue of SUSTAINABILITY, which contains the best papers presented at the Congress. The Special Issue will include the best papers presented at the Congress. These were selected by the Scientific Committee with the help of the various Chairmen of the Sessions. The papers cover all the various aspects of sustainability, from an interdisciplinary point of view, with a strong emphasis on the link between energy production, use and conservation, and environmental impact.